Portrait of Italian Cardio-Oncology: Results of a Nationwide Associazione Nazionale Medici Cardiologi Ospedalieri (ANMCO) Survey - Canale, Maria Laura; Turazza, Fabio; Lestuzzi, Chiara; Parrini, Iris; Camerini, Andrea; Russo, Giulia; Colivicchi, Furio; Gabrielli, Domenico; Gulizia, Michele Massimo; Oliva, Stefano; Tarantini, Luigi; Maurea, Nicola; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: Cardio-oncology has achieved a pivotal role in science, but real world data on its clinical impact are still limited. Methods: A questionnaire was sent out to all cardio-oncology services across Italy (n = 120). The questionnaire was made up of 28 questions divided into four blocks: (A) general information on hospitals and service, (B) the inner organization of cardio-oncology and its relationships with out-of-hospital cardiologists and general practitioners, (C) educational needs and referral guidelines, and (D) activities/specific workload. Results: Ninety-six out of 120 (80%) completed the questionnaire; 9.4% were cancer centers while 90.6% were general hospitals. A cardio-oncology team was present in 56% of the cancer centers and in 20% only of general hospitals, and a cardio-oncology pathway was active in 55% of cancer centers and in just 14% of the general hospitals. Relationships with out-of-hospital cardiologists and general practitioners were lacking. The guidelines of reference were ESC and ANMCO/AIOM. Patients receiving anthracycline chemotherapy underwent scheduled monitoring by means of echocardiography in 58% of cases. Routine use of cardiac damage biomarkers was overall low, ranging from 22 to 33% while the use of global longitudinal strain reached 44%. Conclusions: Italian cardio-oncology showed a growing influence on clinical practice but still has room for improvement. Cardio-oncology teams are still scarce, and the application of dedicated paths is poor. The need for specific training has been highlighted.